'Anytime, anywhere': vaping as social practice. Issue 4 (8th August 2017) - Keane, Helen; Weier, Megan; Fraser, Doug; Gartner, Coral
Abstract: This article examines the use of e-cigarettes, or vaping, as a social practice. It builds on recent work which argues that theories of social practice can provide effective new ways of conceptualising and responding to public health challenges such as smoking and sedentariness by shifting the focus from individual behaviour. Instead these theories attend to the development and persistence of practices which are enacted across time and space. The article draws on data from a 2014 online survey of Australian vapers, specifically responses to open-ended questions about vaping and its place in daily life. It highlights the way vaping has been established as a practice through a range of factors including the increasing burdens of smoking and the online availability of e-cigarettes and vaping information and advice. Most survey respondents were positive about vaping and constituted it as the opposite of smoking in its ability to improve well-being and transform life for the better. In contrast to smoking, vaping was presented as a practice which opened up space and time, for example as inside the home became a location where nicotine could be consumed. The article also examines the way vaping enables nicotine addiction to be experienced differently, as a form of habitual consumption in which elements of control and choice remain present. The article is limited by its reliance on written responses and the non-representative nature of the survey sample, however it suggests the benefits of naturalistic research on vaping as a social practice.